How does the double-track human resource management model contribute to job burnout and mental health among Chinese government departments? A Chinese police study - Liang, Zhengyan; Yao, Min; Li, Hao; Chen, Jiayu; Yang, Mei; Tang, Tian; Ye, Hong; Zeng, Yuqing; Zhang, Minqiang (Frontiers in Public Health, 2024)
Objectives: This study aims to investigate the contribution of the double-track human resource management model to the job performance and mental health of front-line police within China's public security organs.Methodology: An individual-centered approach, Latent Profile Analysis (LPA), was utilized in this study, which used cluster sampling to survey all police of all 118 front-line police stations an economically underdeveloped area of China and 839 personnel were selected for analysis. This method allowed for a detailed examination of the contribution of the double-track system to job performance and mental health.The study identified three subtypes of job burnout among Chinese police: low job burnout, medium job burnout, and emotional exhaustion type. The double-track human resource management model in China's public security organs has contribution to significant disparities between civilian and auxiliary police, such as more severe job burnout among civilian police, lower job performance and mental health among auxiliary police.Implications: To mitigate the potential risks associated with the double-track human resource management model, adjustments are necessary in both the management system and the treatment distribution system, which would also help address the disparities and improve the overall well-being and performance of all police officers.